المعالجات المحاسبية والاجراءات الرقابية للمنح والمساعدات الحكومية بين التطبيقات الدولية والمحلية / Accounting processes and control procedures for grants and government assistance between international and domestic applications (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
The issue of grants and government assistance is one of the most important topics in our societies and is one of the most important sources of funding in the economic units to help them develop and improve their productivity, as well as help them to compete and continue their economic activity and provide the best services to the society. Therefore, the research reviewed the concept of grants and government assistance and grants, aid and government subsidies, and what concerns the provision of government grants for economic units, and to identify the most important conditions to be met when government grants, and what exceptions to government grants, as well as The study reviewed accounting treatments and monitoring procedures in the registration and follow-up of grants and government assistance in accordance with International Accounting Standard No. 20, US Standard No. 116, Egyptian Standard No. 12 and Saudi Standard No. 18 as well as administrative and accounting procedures taken by the units the Iraqi government in the registration of government grants, the researcher has reached several conclusions, including the absence of an Iraqi accounting standard deals with government grants in the accounting records and how to control and control and classified by nature The purpose for which it has allocated for it, and accounting treatments lacking in the Iraqi government units to the classification of government grants by international standards, as well as the lack of follow-up by the official Iraqi authorities on government institutions that received government grants from third parties and government grants have been spent for the purpose for which allocated , as well as the absence of Iraqi accounting processors are supported by the official authorities of the granting of government in accordance with international accounting standards for grants and government aid through which control these grants and disclosed in the official annual reports, as a Maximum of the researcher several recommendations of the most important Iraqi official bodies related to the financial such as the Ministry and the Federal Office of Finance and the Ministry of Planning Control issued an accounting standard Iraqi special government grants and aid, as well as should be classified as grants received from third parties according to their nature and purpose for which it has allocated to it in accordance with international standards adopted, and the disclosure of grants government received from third parties in the accounting records and disclosure requirements or associated with the government grant to determine the extent of the application of those conditions that have been created restrictions of the grant is received, as well as the need for the Iraqi regulatory authorities Follow-up government grants received from third parties and that have been recorded in the accounting records and disclosure has been completed official institutions received government grants for the purpose and the conditions for which the grant was received.